A study on the potential determinants of green idea in customer's purchasing decision-making process through the grey analytical network process (GANP) evaluated model. (1st January 2012) - Hsieh, Ming-Yuan
This study attempts to cross-integrate the relation quality (RQ) and the consolidated measurements of the analytical network process (ANP) and grey analytical network process (GRA) in order comprehensively discussing the potential determinants of the green idea on customer's purchasing decision-making behaviours. As a result of the hierarchically and systematically evaluated measured consequences, 'green idea does positively trigger customer's consumption'. The most contribution of this study is not only to academically re-supply the traditional research assumption-gap that the customers may be stimulated by the green idea but also empirically offer the enterprises to re-consider and re-position the importance of the green potential effects; especially, the extensive customers have play the most decisive role in this customer-oriented diversified global market.